Pengembangan Formula Enteral Rendah Indeks Glikemik Berbasis Pangan Lokal Labu Kuning, Ubi Jalar Putih dan Susu Kedelai - Nabila, Aprodhit Justicia; Nur Widiyaningsih, Endang; Sarbini, Dwi (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
Diabetes mellitus is a disease in Indonesia whose prevalence will continue to increase. Local food has the potential as an antidiabetic and antihyperglycemic. Pumpkin contains antioxidants that play a role in lowering blood sugar. In addition, fiber intake through nuts can help lower HbA1c levels. The purpose of this study was to determine and analyze viscosity, osmolality, flowability, nutritional content, and organoleptic tests. This study used an experimental method, by making 2 formulas and determining F2 as the recommended formula. The results of the analysis of nutritional substances were 1008.7 kcal of energy, 54.3 grams of protein, 29.5 grams of fat, 136.3 grams of carbohydrates, glycemic index 25.1, viscosity test 909.6 cP, osmolality 368 mOsm/Kg, flowability 0.01 cc/second, and no sediment. This enteral formula has the potential as a low glycemic index enteral food